General Reference Clauses in the Judicial Process Context of Legislative Intentions and Interpretative Discretion - Leszczynski, Leszek; Leszczynski, Leszek; Jaron, Anna (Peter Lang, 2021)
The purpose of this work is to analyze the functioning of extra-legal references (general clauses) in the context of the relation between the legislative policy of opening the legal system and judicial discretion in the field of law interpretation. This publication is based on the analysis of normative acts (in Poland and other selected European countries) and judicial decisions (mainly Polish). The result of the study is an attempt to settle the scope of judicial discretion in determining the content of reference criteria, the basis for their application, and their role in various stages of the process of judicial interpretation of the law. The book concludes with an attempt to construct a comparative and an optimization model of the functioning of general clauses in the legal order.